The Politics of Withdrawal - Marijanovic, Dan (My University, 2024)
This dissertation begins with examining prominent conceptualizations of politics in order to underline a common assumption implicit across all of them: that politics necessarily involves engagement in one form or another, with or against the established political institutions of the state. This assumption has largely occluded acceptance of withdrawal as an alternate way to think and act politically. Recent literature has begun to show how acts of withdrawal may be understood to be politically relevant. There are two issues that plague this literature, however. It does not always make it sufficiently clear what makes withdrawal political in its own right, and a good portion of the literature that attempts this does so by putting it in direct relation to the state, in effect constraining a fuller appreciation of withdrawal as a novel and distinctive way of acting politically. This dissertation aims to contribute to the growing literature on political withdrawal by making it clear what makes instances of withdrawal political in the first place, even when there is either no discernible relation to the state or is conducted in express refusal of the state and its institutions. It does this by utilizing the prominent approaches to politics outlined at the outset of the dissertation. In arguing for the political nature of withdrawal, this dissertation hopes to expand our common understanding of politics, and thus widen the scope of both political action and thought.
Keywords: Withdrawal; Exit; Politics; Political Philosophy; Political Theory; The Political